(3cJGH GdSQ Gdecfhf aj efGbH GdYGQa HGddg JYGdi Pi Gdfhfs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hSdGe Ydi YHGOg GdPjf EUWai gPG cJGH SejJg GdSQ Gdecfhf ai efGbH Pi Gdfhf bGd CHh YHO GdQMef eMeO Hf GdMSfj GdSdei ai WHbGJ GdUhajI Ph Gdfhf EHQGgje GdeUQi CHh GdajV hjbGd KhHGf Hf EHQGgje hPh Gdfhf dbH s
(3BNQgG (B:s
(3afGOi ef Vjb WQjbkG adG LgGO dg GfJgi hGddg CYde Je GdcJGH HYhf Gdedc GdhgGH hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hCRhGLg hPQjJg hCfUGQg hCgd HjJg hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJUha hGdBOGH GdTQYjIs